ANALISIS BANTUAN KEUANGAN PROVINSI JAWA TENGAH KEPADA PEMERINTAH DESA UNTUK PENINGKATAN KETAHANAN MASYARAKAT DESA (PKMD) DI KABUPATEN KARANGANYAR TAHUN 2020 - Dwi Prihanto (Master of Public Administration, Universitas Slamet Riyadi, 2021)
The purpose of this study is to determine the effectiveness of the assistancein Improving the Village Community Resilience (PKMD) of 2020. The policy ofusing Financial Assistance for the Village Governments for PKMD activities in2020 was directed at the capital participation of BUMDesa to develop a villagefood-business unit as a provider of basic food-necessity for the community. Themethod used is descriptive qualitative by using management actuating principlesfrom Terry & Leslie in the implementation process. While to see its effectivenessthe researcher used the Kenneth Boulding system schema approach with inputprocess-output. The data collection technique used is interviews anddocumentation. The implementation of the financial assistance for PKMD inKaranganyar Regency has been implemented properly according to theregulations. From the input indicator to the actualization which becomes thebenchmark of the research, the actualization of this financial assistance has not metthe maximum results yet, especially in the purpose of assistance, meeting the needsof cheap basic-necessities for the village residents affected by Covid. Because, inthe distribution process, there are no strict rules from the village about who isallowed to buy cheap basic-necessities, everything is being entrusted to the villagestalls as sales-partners of Bumdesa.Keywords: Effectivity, Financial Assistance, Community Resilience